First report of Xylella fastidiosa infecting coffee in Costa Rica - Rodríguez Solís, Carlos Mario (2001)
In 1995, severe symptoms were observed on ‘Caturra’ and ‘Catuaí’ coffee (Coffea arabica L.) varieties in farms in the southern part of the Central Valley in Costa Rica. Symptoms were reduced leaf size, malformation of leaves, curling of leaf edges, shortening of internodes, and severe leaf chlorotic mosaic, which sometimes became necrotic. Abortion of flowers and young beans was also observed, with a reduction in yield. Plants also showed irregular growth with an atypical curling appearance that gave rise to the Spanish name “crespera.” Ten and three healthy plants were inoculated by grafting in the greenhouse, using infected and healthy budwoods, respectively. Approximately 6 months after inoculation, 3 of 10 grafted plants with infected budwoods showed symptoms of leaf chlorosis, curling, and malformation of leaves and bunched new flushes. Samples of 39 symptomatic plants collected from the field and samples of 3 healthy plants maintained in the greenhouse were tested by enzyme-linked immunosorbent assay (ELISA). All (100%) analyzed symptomatic samples were positive for X. fastidiosa, and all healthy controls were negative. The symptoms observed in Costa Rica are different from those described for coffee leaf scorch in Brazil (1,2), but the climatological conditions and soil type present in Costa Rica are also very different from the areas where X. fastidiosa occurs in Brazil. Leafhoppers were collected randomly in one of the most affected regions. Graphocephala permagna and Erythrogonia sonora were the most frequent insect species found associated with coffee. In ELISA, 34.5% (10 of 29) and 23.8% (5 of 21) of the collected specimens belonging to G. permagna and E. sonora, respectively, tested positive for X. fastidiosa. These positive ELISAs do not necessarily mean that the insect is a vector. The results presented here extend the known geographic distribution of X. fastidiosa. To our knowledge, this is the first report of X. fastidiosa in coffee in Costa Rica.